Harmonization of Competition Law: Research on The Transplantability of eu’s Law into ASEAN - Reni Budi Setianingrum; M. Hawin (Universitas Airlangga, 2020)
ASEAN has agreed to run a single market through the ASEAN Economic Community (AEC). The consequence of this free flow of goods and services is the emergence of new business competition, new relevant markets and potential contact amongst business actor of ASEAN member and it is possible to create unfair business competition. The implementation of the AEC also has consequences in the field of regulation, specifically the need for harmonization of regulations on competition law in ASEAN member to overcome the problems of cross-border transactions and the absence of competition law in several ASEAN member. This study uses a normative juridical method and aims to examine harmonization of competition law, a research on the transplantability of EU’s law into ASEAN. Results of this research shows that ASEAN can only adopt the European Union's supranationalism system only for cases of violations of cross border competition law, whereas for cases of violations of national competition laws, each country is given sovereignty to apply its own law. This is because the economic characteristics and legal characteristics of business competition vary between ASEAN member countries.